2004
DOI: 10.1111/j.1471-0528.2004.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between delivery mode and mortality in very low birthweight singleton vertex‐presenting infants

Abstract: Objective  To investigate the factors associated with caesarean delivery and the relationship between mode of delivery and mortality in singleton vertex‐presenting very low birthweight (≤1500 g) live born infants. Design  Observational population‐based study. Setting  Data collected from all 28 neonatal departments comprise the Israel National Very Low Birth Weight Infant Database. Population  2955 singleton vertex‐presenting very low birthweight infants registered in the database from 1995 to 2000, and born a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
55
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 31 publications
(49 reference statements)
8
55
4
1
Order By: Relevance
“…1 The optimal route of delivery for the early preterm fetus remains controversial. Some observational studies have shown a lower neonatal mortality for planned cesarean delivery as compared with vaginal delivery for vertex [2][3][4] and breech early preterm pregnancies 2, 4-9 whereas other studies do not show a difference by route of delivery for vertex [10][11][12] or breech presentation. [13][14][15] The vertical uterine incision often required for cesarean delivery at this gestational age increases the risks of hemorrhage, bladder injury and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…1 The optimal route of delivery for the early preterm fetus remains controversial. Some observational studies have shown a lower neonatal mortality for planned cesarean delivery as compared with vaginal delivery for vertex [2][3][4] and breech early preterm pregnancies 2, 4-9 whereas other studies do not show a difference by route of delivery for vertex [10][11][12] or breech presentation. [13][14][15] The vertical uterine incision often required for cesarean delivery at this gestational age increases the risks of hemorrhage, bladder injury and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Lee at al showed a decrease in mortality with vaginal delivery in appropriately grown preterm neonates (3). Other studies have found no significant difference between cesarean and vaginal deliveries with regard to neonatal outcomes in appropriately grown premature neonates (4,5,6). Even in small for gestational age neonates, a prior study by the authors of this paper found no difference in neonatal outcomes between cesarean and vaginal deliveries except with regard to neonatal respiratory distress, which was moderately decreased with vaginal delivery (7).…”
Section: Introductionmentioning
confidence: 59%
“…Very recently, in France, a study of 626 singleton breech-presenting premature infants at [26][27][28][29] +6 GW reported that the mode of delivery was not related to mortality (24). In a retrospective study of a very large series, 1854 premature babies who were born on the edge of life (23-24 GW) were examined, and it was determined that the mode of delivery did not affect mortality in breech-presenting babies with birth weights <500 g and in newborns intubated for 6 months (25).…”
Section: Breech Presentation and Mortalitymentioning
confidence: 99%
“…Riskin et al (27) indicated that in 2955 singleton vertex-presenting infants born with <1500 g birth weights at 24-34 GW, cesarean section did not prevent mortality after a logistic re-gression analysis. Thus, unless an obstetric indication is present, cesarean section should not be recommended in premature babies.…”
Section: Singleton Vertex Presentation and Mortalitymentioning
confidence: 99%